1981
DOI: 10.1126/science.7233220
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidate as a Molecular Link Between Depolarization and Neurotransmitter Release in the Brain

Abstract: Phosphatidate, a neuronal phospholipid, stimulated the uptake of calcium by nerve terminals isolated from the striatum of rat brain. This effect was not produced by other phospholipids or glycolipids. Phosphatidate, but not other phospholipids, evoked the release of [3H] dopamine from striatal synaptosomes. The magnitude of both effects was similar to that observed after chemical depolarization of the nerve terminals. These results show that phosphatidate is the only membrane lipid component that acts as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

1982
1982
2000
2000

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…Salmon and Honeyman (1980) proposed that increased phosphatidate may mediate the increased cellular Ca ++ levels produced by cholinergic stimulation and noted that phosphatidate at concentrations as low as 10~8 M produced contractions in isolated smooth muscle cells. Phosphatidic acid has been proposed as a Ca ++ ionophore in the promotion of Ca ++ uptake in isolated nerve terminals (Harris et al, 1981) and in liposomes (Serhan et al, 1982). By contrast, an ionophoretic action of phosphatidic acid could not be demonstrated in another liposomal membrane model (Holmes and Yoss, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Salmon and Honeyman (1980) proposed that increased phosphatidate may mediate the increased cellular Ca ++ levels produced by cholinergic stimulation and noted that phosphatidate at concentrations as low as 10~8 M produced contractions in isolated smooth muscle cells. Phosphatidic acid has been proposed as a Ca ++ ionophore in the promotion of Ca ++ uptake in isolated nerve terminals (Harris et al, 1981) and in liposomes (Serhan et al, 1982). By contrast, an ionophoretic action of phosphatidic acid could not be demonstrated in another liposomal membrane model (Holmes and Yoss, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of PA, which is a weak ionophore as compared to A23187, has been postulated to function in Ca 2+ gating at the plasma membrane [113,177,224,237,242,268,319]. The formation of PA, which is a weak ionophore as compared to A23187, has been postulated to function in Ca 2+ gating at the plasma membrane [113,177,224,237,242,268,319].…”
Section: Inositol Trisphosphate In Calcium Mobilizationmentioning
confidence: 99%
“…A question might be raised as to whether the inhibitory activity of Ca2+ on the enhancement of GABA uptake by PS may have originated from the facilitation of GABA efflux. This possibility is not likely, as recent work in our laboratory (unpublished data) and by others (Harris et al, 1981) has shown that PS is not involved in the release of GABA and dopamine. Nipecotic acid, which is known to be a potent inhibitor of GABA uptake (Krogsgaard-Larsen and Johnston, 19751, has been suggested as a substrate for the GABA transport carrier (Johnston et al, 1976;Larsson et al, 1980).…”
Section: Discussionmentioning
confidence: 79%